2019
DOI: 10.33494/nzjfs492019x51x
|View full text |Cite
|
Sign up to set email alerts
|

Allometric biomass equations for young trees of four broadleaved species in Albania

Abstract: Background: Biomass assessment of young forest stands is important because of their role in the carbon cycling. The aim of this study was to develop biomass equations for young broadleaved species growing in natural conditions in Albania. Methods: Five forest stands were investigated using circular sample plots. Diameter at breast height (DBH) and height (H) from 58 sampled trees ranging in age from 4 to 34 years old of Turkey oak (Quercus cerris L.), sweet chestnut (Castanea sativa Mill.), European horn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In the case of C. mopane species in Mozambique, this study found that the model that included the interaction of D 2 and H performed better than the model that used separate D and H variables, suggesting a non-linear relationship between D and H. However, models that included both D and H performed similarly to models that used only diameter, suggesting that including H as an explanatory variable did not significantly improve the biomass estimation accuracy for C. mopane species. This result is consistent with previous studies16,56 . The results of AGB estimation showed that the inclusion of H data from the H-D model in Model 3 for AGB estimation resulted in higher error propagation compared to Model 1, which used only D as an explanatory variable.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…In the case of C. mopane species in Mozambique, this study found that the model that included the interaction of D 2 and H performed better than the model that used separate D and H variables, suggesting a non-linear relationship between D and H. However, models that included both D and H performed similarly to models that used only diameter, suggesting that including H as an explanatory variable did not significantly improve the biomass estimation accuracy for C. mopane species. This result is consistent with previous studies16,56 . The results of AGB estimation showed that the inclusion of H data from the H-D model in Model 3 for AGB estimation resulted in higher error propagation compared to Model 1, which used only D as an explanatory variable.…”
supporting
confidence: 94%
“…Including estimated H in BAE for biomass estimation is controversial in ecological research. While some studies argue that including H improves accuracy 15,54 , others suggest that it may lead to an underestimation of carbon storage 55 or may not improve accuracy at all 16,56…”
Section: Biomass Allometric Equation and Biomass Estimationmentioning
confidence: 99%
“…In the context of the destructive method, a representative sample is importantly required to obtain ideal information related to tree attributes. Most studies generally used diameter distribution since it could also describe the vegetation structure from the sampling location (Altanzagas et al, 2019;Istrefi et al, 2019;Karyati et al, 2021). Moreover, the diameter is a tree parameter that most accurate to measure.…”
Section: Resultsmentioning
confidence: 99%
“…Our study showed that models with H and DBH have higher efficiency for all the studied species and similar findings were also reported by Rutishauser et al (2013); Kusmana et al (2018) and Khushi et al (2019). Allometric models with single independent variable (DBH) are robust in the field measurement and biomass estimation (Ketterings et al, 2001;Chave et al, 2014;Istrefi et al, 2019). But, DBH as single independent variable has shown lower efficiency in model selection parameters of this study.…”
Section: Discussionmentioning
confidence: 81%